Change in Sexual Functioning during the Aging Process - Nascimento, Leonardo Goodson do (Revista Brasileira de Sexualidade Humana, 1993)
YOUNG, W. R. Change in sexual functioning during the aging process. In: Bianco, F. J. and cols. Sexology: an independent field. 121-128, 1990.